Energy Expenditure in Rock/Pop Drumming - De La Rue, S E.; Draper, S. B.; Potter, C. R.; Smith, M. S. (International Journal of Sports Medicine, 2013)
Despite the vigorous nature of rock/pop drumming, there are no precise data on the energy expenditure of this activity. The aim of this study was to quantify the energy cost of rock/pop drumming. Fourteen male drummers (mean±SD; age 27±8 yrs.) completed an incremental drumming test to establish the relationship between energy expenditure and heart rate for this activity and a ramped cycle ergometer test to exhaustion as a criterion measure for peak values (oxygen uptake and heart rate). During live concert performance heart rate was continuously measured and used to estimate energy expenditure (from the energy expenditure vs. heart rate data derived from the drumming test). During concert performance, estimated energy expenditure (mean±SD) was 623±168 kcal.h−1 (8.1±2.2 METs) during performances of 38.6±15.6 min, and drummers achieved a peak heart rate of 186±16 b.min−1 During the drumming test participants attained 78.7±8.3% of the cycle ergometer peak oxygen uptake. Rock/pop drumming represents a relatively high-intensity form of physical activity and as such involves significant energy expenditure. Rock/pop drumming should be considered as a viable alternative to more traditional forms of physical activity.
Keywords: exercise physiology; physical activity; heart rate; music